Job Autonomy on Psychological Well-Being: The Mediating Role of Leisure Activities - Rui Dong; Lingling Song; Yuxi Yang; Shiguang Ni (SAGE Open)
Leisure and work are two important aspects of human well-being. However, most studies on individuals’ psychological well-being have examined these aspects independently, based on either job characteristics or a leisure perspective. In this study, we used a unified theoretical framework of the physical activity-mediated demand–control model to explore the impacts of job characteristics and leisure activities on people’s psychological well-being. Over 4 weeks, 662 Chinese employees completed two waves of time-lagged surveys with items measuring job autonomy, leisure activities, life satisfaction, and emotional exhaustion. The results showed that job autonomy increases employees’ life satisfaction while decreasing emotional exhaustion. Moreover, leisure activities mediate the relationships between job autonomy, emotional exhaustion, and life satisfaction. This paper adopted the comprehensive framework to integrate job characteristics and leisure activity research areas and revealed a work-to-leisure positive spillover effect.